Differences in The Effects of 15% Moringa Leaf (Moringa oleifera) Extract Gel and 70% Kecemcem (Spondias pinnata) Tree Bark on Gingiva Angiogenesis of Wistar Rats Post Curettage with Periodontitis Conditions - Eka Pramudita Ramadhany; Ni Luh Desy Ayu Susilahati; Putu Vinia Suryawan (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Periodontitis, with a fairly high prevalence in the world, drives the need for periodontal treatment. Adjuvant therapy is needed in curettage treatment in periodontitis patients to accelerate the wound healing process. Moringa leaf extract and kecemcem tree bark have efficacious content as antioxidants, anti-inflammatories, and wound healing properties. This study aims to determine the difference in the effect of 15% moringa leaf extract gel and 70% kecemcem tree bark on gingival angiogenesis in Wistar rats after curettage with periodontitis conditions. Materials and Methods: Wistar rats were divided into four groups: negative control (CMC-Na), positive control (hyaluronic acid), moringa leaf treatment, and kecemcem tree bark treatment. Periodontal pockets were induced by tying a silk thread to the mandibular incisors, then curettage was performed with a Sub-Zero curette (Osung). The mice were applied with gel types according to the group, then sacrificed on days 3, 5, and 7. Histological preparations were made for observation in three different fields of view using a light microscope with a magnification of 400x. Results and Discussion: The Average amount of angiogenesis in the kecemcem tree bark treatment group was higher than in all treatment groups. LSD results showed that there was a significant difference (p<0.05) between all treatment groups. Kecemcem tree bark gave higher results in increasing the amount of angiogenesis due to significant differences in concentration and the high content of β-sitosterol, which affects angiogenesis. Conclusion: There is a difference in the effect of 15% moringa leaf extract gel and 70% kecemcem tree bark on gingival angiogenesis in post-curettage Wistar rats with periodontitis conditions. Application of 70% kecemcem tree bark extract gel gave a better effect in increasing the amount of gingival angiogenesis in Wistar rats after curettage with periodontitis conditions.